REFRACTORY THYROTOXICOSIS - CHALLENGES IN MANAGEMENT - MJ, Nurafna; A, Nida' Ul-Huda; CV, Tong (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Refractory Graves thyrotoxicosis is a rare condition in which hyperthyroidism fails to respond to the conventional thionamides. Patient with severe hyperthyroidism or allergy to thionamide may benefit from alternative medical therapies namely radioactive iodine therapy, glucocorticoids, cholestyramine or lithium. Thyroidectomy is the definitive treatment for Graves thyrotoxicosis that is recommended when medical therapies have failed or are contraindicated. The medical records of the patient were traced and reviewed. CASE Here we report a 14-year-old girl who was diagnosed with Graves' disease a year ago. She had thyrotoxic symptoms with positive thyroid autoantibodies. She was initially started on carbimazole and developed agranulocytosis from it. She had cushingoid syndrome with myopathy from steroid, gastrointestinal side effects from cholestyramine and severe lithium toxicity requiring hemodialysis. She developed severe myopathy compromising her airway and requires mechanical ventilation and needed prolonged intubation. She was initially planned for radioactive iodine therapy but remained clinically and biochemically hyperthyroid despite trial of 4 cycles of plasmapheresis. The only therapy that managed to control her hyperthyroidism temporarily was Lugol’s iodine. Thus the initial plan for radioactive iodine treatment was not feasible. In general, we would usually aim for patient to be in euthyroid state prior to surgery to minimize potential peri-operative complications. A short course of Lugol’s iodine was reinitiated and she was referred for inpatient thyroidectomy. She successfully underwent thyroidectomy without any peri-operative complications and is currently in euthyroid. CONCLUSION In conclusion, inpatient thyroidectomy should be considered in patient with refractory Graves thyrotoxicosis that is resistant to conventional therapies to prevent secondary complications.